UNLOCKING THE POTENTIAL OF AGRICULTURE WASTE AS A SOIL AMENDMENT ON GROWTH PERFORMANCE OF SWEET CORN (Zea Mays.) - Noor Sharina Mohd Rosli; Norazlina Abu Sari; Nur Maizatul Idayu Othman (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The decline in soil fertility of agricultural land and the abundance of agricultural wastes is a major problem in the environment. To overcome these problems, agricultural wastes have the potential to serve as a beneficial product that provides sustainable agriculture. The use of agricultural wastes as soil amendments is a sustainable practice in improving soil quality and plant productivity. Therefore, this study was carried out to evaluate the potential of agricultural wastes and agriculture wastes-derived biochars as soil amendments toward sweet corn (Zea Mays.) growth performance. The study was conducted in the greenhouse for 75 days. A randomized complete block design with four treatments (oil palm empty fruit bunch (EFB), EFB biochar, decanter cake, corn cob and corn cob biochar) in combination with mineral soil and four replication was used during the study. Plant height, stem diameter, and number of leaves were assessed for each treatment. Results indicate that corn cob biochar significantly increased the sweet corn height and plant diameter by respectively 11.0% and 25.0% as compared to the control. An increase in the stem diameter by 10.0% due to the application of EFB was observed at 45 days compared to the other treatments. In conclusion, the agricultural waste which is corn cob biochar were observed to have the potential in enhancing the sweet corn (Zea Mays.) growth.